(untitled) (Heritage, 2026)
The director of a limited liability company in the Republic of Serbia has a key role in the management and representation of the company, whereby his powers, responsibilities and legal position arise from the Companies Law and other relevant regulations. The paper analyzes the legal status of the director, including the manner of appointment and dismissal, authority in the management of affairs, responsibility for the legality of business, as well as his employment status, which can be regulated by an employment contract or a contract on rights and obligations. Special emphasis is placed on the responsibility of the director, which can be property, criminal and misdemeanor, and refers to bookkeeping, representation of the company, reporting obligation, avoidance of conflict of interest and compliance with the prohibition of competition. Although the director has broad powers, they are at the same time limited by the decisions of the founder, the general meeting or the supervisory board, which in practice can lead to dilemmas regarding his actual autonomy in making business decisions. The law sets minimum standards for the responsibility of directors, but the company's acts may provide for stricter conditions, thereby increasing the degree of its liability. Although the director is formally the highest executive body of the company, his actions are under the constant supervision of the founders and governing bodies, which further emphasizes the complexity of his legal position. In this sense, further analysis and potential changes to the legislation could contribute to a more precise definition of the relationship between directors, founders and other bodies of the company, which would improve legal certainty and efficiency of corporate governance in limited liability companies in the Republic of Serbia.